Social media content management on Instagram in the fashion industry - Lubna Haya; Anisa Diniati (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2024)
The management of Instagram social media content for Palugada Streetwear as a retail fashion streetwear brand has resulted in rapid growth, reaching two million accounts, a surge of up to 524%, and a significant increase in engagement by 21.7 thousand accounts. This research aims to comprehend how Instagram content management in the fashion industry enhances customer engagement. Researchers employ the POST social media management theory (KOMINFO, 2018) and the social action theory for amplifying customer engagement (Evans & McKee, 2010). Using a qualitative approach, data is gathered through interviews with Palugada's CEO and Head of Marketing, academicians who are social media experts, and Palugada Instagram account followers. In addition to interviews, observation and document analysis are also conducted. Research findings reveal that Palugada implements six content management stages, including determining target audience characteristics, establishing objectives through 4 content pillars, setting an editorial plan, formulating KPIs, executing content management strategies, and distributing content. The fifth phase involves specific strategies, including research, curation, content production, collaboration, and media monitoring.